Organizing and personalizing intelligence gathering from the web - ONG, Hwee-Leng (Institutional Knowledge at Singapore Management University, 2002)
In this paper, we describe how an integrated web‐based application, code‐named FOCI (Flexible Organizer for Competitive Intelligence), can help the knowledge worker in the gathering, organizing, tracking and dissemination of competitive intelligence (CI). It combines the use of a novel user‐configurable clustering, trend analysis and visualization techniques to manage information gathered from the web. FOCI allows its users to define and personalize the organization of the information clusters according to their needs and preferences into portfolios. These personalized portfolios created are saved and can be subsequently tracked and shared with other users. The paper runs through an example to show how the use of a predefined domain template coupled with personalization can greatly enhance an organization and tracking of CI gathered from the web.